The efficacy of bevacizumab combined with platinum-containing chemotherapy in the treatment of advanced non-small cell lung cancer in China: a systematic review and meta-analysis of randomized clinical trials - Han, Guangsu; Li, Chenlu; Yi, Ping (Frontiers in Pharmacology, 2024)
Background: Platinum-based dual-drug first-line chemotherapy is commonly employed in the treatment of patients with advanced non-small cell lung cancer (NSCLC), although its clinical efficacy is limited. Bevacizumab can antagonize vascular endothelial cell growth factor (VEGF), which inhibit tumor angiogenesis and prevent tumor invasion and development. However, a comprehensive meta-analysis evaluating the effectiveness and safety of combining bevacizumab with platinum-based chemotherapy in advanced NSCLC patients is lacking.Methods: Randomized controlled trials (RCTs) investigating the combination therapy of bevacizumab and platinum-based chemotherapy for treating advanced NSCLC were searched across six databases. Data on objective response rate (ORR), disease control rate (DCR), one-year survival rate, two-year survival rate, three-year survival rate, VEGF levels, and side effects were synthesized. Relative risk degree (RR) along with 95% confidence interval (CI) was used as statistical analysis measures for binary outcomes while continuous variables were analyzed using mean difference (MD) along with 95% CI. Heterogeneity was evaluatedtested by Chi-squared and I 2 tests. If there was heterogeneity, subgroup analysis was performed.Sensitivity analysis of the main outcome measures and assessment of publication bias were also performed.Results: According to our screening criteria, a total of Forty-nine RCTs were included, involving data from 4268 patients. The results of this analysis showed that compared with platinum-containing chemotherapy alone, bevacizumab combined with platinum-containing chemotherapy significantly improved ORR (RR [95% CI], 1.53 [1.44, 1.63], p < 0.00001), DCR (RR [95% CI], 1.24 [1.19, 1.29], p < 0.0001), one-year survival rate (RR [95% CI], 1.34 [1.15, 1.57], p= 0.0003), two-year survival rate (RR [95% CI], 2.16 [1.35, 3.43], p= 0.001), three-year survival rate(RR [95% CI], 2.00 [1.21, 3.30], p= 0.007). In addition, bevacizumab with platinumcontaining chemotherapy observably decreased the VEGF levels (RR [95% CI], -67.35 [-91.46, -43.25], p<0.00001).Combination therapy involving bevacizumab demonstrated improved antitumor effects compared to chemotherapy alone in terms of ORR, DCR, one-year survival rate, twoyear survival rate, three-year survival rate, and VEGF levels without an increased incidence of adverse reactions. These analyses' results can provide clinicians guidance when selecting appropriate treatments for patients diagnosed with advanced non-small cell lung cancer.